Analysis of High School Students' Perceptions of Continuing Studies at State Universities - Sutirna Sutirna; Oktaviarini Yahya Ramadhanty; Sayyid Agil Rifqi Munawar; Aneu Pebriani (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze high school students' perceptions of continuing their studies at state universities based on internal and external factors. This research employed a survey approach involving Grade XII students from public and private high schools in Karawang Regency. The research instrument consisted of a questionnaire with 40 statement items covering internal and external indicators, supported by interviews with selected respondents. Data were analyzed using descriptive percentage analysis to determine the level of students' interest and the influencing factors. The results of the study indicate that both internal and external factors fall into the "very low" category, showing that students' interest in continuing to higher education is generally weak. Internal factors such as motivation, self-confidence, and career planning were found to be low, while external factors including family economic conditions, parental support, peer influence, and limited access to information significantly affect students' decisions. Interview findings also reveal that many students prefer to enter the workforce immediately after graduation to support their families financially, although some still aspire to pursue higher education in the future. In conclusion, students' low interest in continuing to higher education is influenced by a combination of internal and external factors, with economic conditions being the most dominant. Therefore, it is recommended that schools, the government, and relevant stakeholders strengthen guidance programs, provide access to scholarships, and raise awareness of the long-term benefits of higher education to encourage students to pursue further studies.